Menthol- and thymol-based ciprofloxacin derivatives against Mycobacterium tuberculosis: in vitro activity, lipophilicity, and computational studies - Daniel Szulczyk; Mateusz Woziński; Michał Koliński; Sebastian Kmiecik; Agnieszka Głogowska; Ewa Augustynowicz-Kopeć; Michał A. Dobrowolski; Piotr Roszkowski; Marta Struga; Krzesimir Ciura (Scientific Reports, 2023)
Abstract In this work, we investigated the antitubercular properties of Ciprofloxacin derivatives conjugated with menthol and thymol moieties. For the sixteen derivatives, we established minimal inhibitory concentrations (MIC) using isolates of Mycobacterium tuberculosis that were resistant or susceptible to other antibiotics. For the most potent compound 1‐cyclopropyl‐6‐fluoro‐7‐{4‐[6‐((1R,2S,5R)‐2‐isopropyl‐5‐methylcyclohexyloxy)‐6‐oxohexyl]piperazin‐1‐yl}‐4‐oxo‐1,4‐dihydroquinoline‐3‐carboxylic acid (6), we determined fractional inhibitory concentration index (FICI) values to confirm antibacterial susceptibility and synergistic effects with other reference drugs. In addition, chromatographic studies of all the derivatives demonstrated a significant three to four-fold increase in lipophilicity and affinity to phospholipids compared to Ciprofloxacin. Finally, we conducted structure-based studies of the investigated compounds using molecular docking and taking into account protein target mutations associated with fluoroquinolone resistance. In summary, our findings indicate that the investigated compounds possess tuberculostatic properties, with some showing similar or even better activity against resistant strains compared to reference drugs. Increased lipophilicity and affinity to phospholipids of the new derivatives can offer several advantages for new drug candidates, beyond just improved cell membrane penetration. However, further studies are needed to fully understand their safety, efficacy, and mechanism of action.